Anthropogenic land uses drive shifts in denitrification‐related microbiota in freshwater river ecosystems. (9th October 2022) - Liu, Xing; Pan, Baozhu; Huang, Zhenyu; Liu, Xinyuan; He, Haoran; Zhu, Xinzheng
Abstract: Microbiota play essential roles in nitrogen (N) cycling in freshwater river ecosystems. However, our understanding of microbial functional groups associated with N cycling (especially denitrification) in freshwater rivers under anthropogenic disturbance is still poor. Here, we studied the impacts of different land‐use types on denitrification‐related microbiota in the Weihe River, Hanjiang River, and their tributaries, in the Qinling Mountains, China. The major land‐use types in the three river areas were divided into natural (forest, shrub, grassland, and open water) and anthropogenic (agricultural and urbanized land) types. A landscape survey of microbiota in the river water and sediment was carried out with extensive sample sources based on deep 16S rRNA gene sequencing, which yielded operational taxonomic units for predicting functional groups. With increases in proportions of agricultural and urbanized land areas, electrical conductivity, total N, ammonium‐N, and nitrate‐N all increased in water samples. Conversely, microbial diversity exhibited a decreasing trend in water samples, whereas the relative abundance of denitrification‐related functional groups increased, with increases in the proportions of agricultural and urbanized land areas. The relative abundances of denitrification‐ and human‐related microbial functional groups in sediment samples were distinctively higher in Weihe River (mainly under agriculture and urbanization), when compared with those of Hanjiang River and Qinling tributaries (dominated by forests). The results indicate that anthropogenic land‐use types, such as agricultural and urbanized land, result in simple microbial community structure and stimulate microbe‐mediated denitrification in freshwater rivers.